Intestinal mucosal lymphocytes in neonatal sepsis - Kh. S. Khaertynov (Rossijskij Vestnik Perinatologii i Pediatrii, 2019)
We studied the autopsy material obtained from 7 children who died in the neonatal period in order to evaluate the composition of lymphocytes of the intestinal mucosa against the background of morphological changes in the tissues of the gastrointestinal tract in newborns with sepsis. The main group consisted of 4 children with neonatal sepsis, the control group – of 3 newborns who died from other causes. The research material included the specimen of the small and large intestine.Results. Small intestine: it was found that there were less CD4 + lymphocytes in the small intestinal mucosa in the group of children who died from neonatal sepsis in 75% of cases than in the control group, but this difference was not statistically significant (p=0.1). There were no differences in the number of CD8 + and CD20 + cells in the studied groups. Large intestine: the number of CD4 + lymphocytes of the mucous membrane of the colon was greater in the main group of children than in the control group (p=0.03). An increase in the number of CD4 + cells was registered in 3 of 4 cases of neonatal sepsis. The number of CD8+ and CD20+ lymphocytes in the studied groups was the same (р>0.05).Conclusion. The increase in T-lymphocytes CD4+ in the mucous membrane of the large intestine is probably connected with the antigenic stimulation of opportunistic intestinal bacteria. We found no morphological signs of the suppression of the cells of adaptive immunity associated with the intestinal mucosa.